Literature Review: Faktor Risiko Penyebab Diabetes Melitus Tipe II pada Remaja - Amanda Maharani S; Mally Ghinan Sholih (Jurnal Sehat Mandiri, 2024)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder that is a growing global health issue. The main objective of this literature review is to identify risk factors that contribute to the development of type 2 diabetes mellitus in adolescents. This study used the literature review method by searching for relevant literature found in the Google Scholar and PubMed databases. From the search, 20 journals that met the relevance criteria were obtained. The data processing process includes several stages: reading, understanding, comparing, and concluding. The research output explained that risk factors that contribute to the development of Diabetes Mellitus (DM) have two categories, namely non-modifiable factors and modifiable factors. Non-modifiable risk factors include gender, age, and family history. On the other hand, modifiable risk factors include obesity, hypertension, physical inactivity, and smoking. In conclusion, adolescents are susceptible to developing type 2 DM, due to complex and diverse risk factors. It is recommended for teenagers to increase awareness of prioritizing a healthy lifestyle by controlling body weight through a balanced diet and regular physical activity, as well as avoiding smoking and managing blood pressure optimally, which can help reduce the risk of DM.